The reality of media education in schools of the second cycle of basic education from the point of view of teachers in the city of Latakia - طواشي, طاهر; رامي أمون (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The study aimed to identify the reality of media education in schools of the second cycle of basic education in the city of Latakia. The study used the descriptive analytical method, where the study sample consisted of (112) male and female teachers in the second cycle of basic education who were selected using a simple random sampling method. The study relied on a questionnaire about the reality of media education prepared by the researcher, which consisted of (37) items distributed over four main dimensions. After verifying the psychometric properties of the tool in terms of validity and reliability, the results of the study showed: The degree of awareness of teachers in the second cycle schools of the basic education stage of the importance of media education was high. It also showed that the degree of teachers’ application of media education activities and the degree of their practice of media education skills was low, while with regard to the obstacles to implementing media education in the schools of the second cycle, it was a high degree. In the end, the researcher recommends, in light of the results of the study, the need to encourage educational departments responsible for developing school curricula to introduce media education into the educational curricula, by integrating the concepts and skills of media education into some academic subjects as classroom or extracurricular activities, based on many experiences in some Arab countries. And global.